Use of Arbuscular Mycorrhizal Fungi and Liquid Organic Fertilizer for Soybean Cultivation on Post-Mining Land: Penggunaan Fungi Mikoriza Arbuskula dan Pupuk Organik Cair untuk Budidaya Kedelai di Lahan Pascatambang Batubara - Kusumawati, Eko; Susanto, Dwi; Nurhikmah, Putri Indah (Universitas Brawijaya, 2025)
Arbuscular mycorrhizal fungi is one of the biological fertilizers defined as inoculants with active ingedients of living organisms that function to tether certain nutrients or facilitate the availability of nutrients in the soil for plants. Organic liquid fertilizer is a solution resulting from the decomposition of organic matter derived from plant residues, animal and human waste that contains more than one element. The addition of arbuscular mycorrhizal fungi and organic liquid fertilizer is expected to improve the plant gowth environment and increase the availability of several nutrients. The purpose of this study was to determine the effect of arbuscular mycorrhizal fungi and the effect of organic liquid fertilizer and their interaction on the gowth of soybean plants (Glycine max L.) gown on post-mining soil. This research was conducted using a 2-factor completely randomized design (CRD) with 3 replications. The treatments consisted of arbuscular mycorrhizal fungi (0, 10, 20, 30, 40g/polybag) and organic liquid fertilizer (0ml, 10ml/plant, 20ml/plant). The results showed that arbuscular mycorrhizal fungi with a single factor and a combination of arbuscular mycorrhizal fungi with organic liquid fertilizer had a significant effect on plant gowth and colonization of soybean plant roots.